Pengendalian Likuiditas Perusahaan Dengan Pengaturan Pickup Service Perbankan Pada KCP Di PT Pos Indonesia Untuk Mencegah Terjadinya Fraud - Sandy Muhammad Kautzar; Syamsul Amry; Vip Paramarta (Lembaga Pengembangan Kinerja Dosen, 2024)
Every business has debts that need to be paid in full and on schedule. But not every business is equally able to cover short-term obligations. If a corporation can effectively manage its liquidity and has good liquidity, it might be considered to have good capabilities. By employing liquidity ratio analysis to determine a company's level of capacity to pay its debts, Furthermore, a business must manage liquidity by examining how to best utilize liquidity in accordance with its responsibility requirements. Additionally, businesses must constantly estimate their cash availability and needs. Analyzing ratios is another way to accomplish it. Liquidity plays a crucial part in demonstrating the performance of the business. Pos Indonesia, a firm, is one that needs to